Introducing the New Evolutionary Paradigm in Anthropology - Jana Baćević (University of Belgrade, 2016)
Why evolutionary psychology now? There is a number of answers to this question. The first and the most obvious one is that this approach is, and, for some years now, has consistently been, gaining prominence in the anthropological circles. However, what I hope the present papers will convey are theoretical, methodological and/or interpretive tendencies that are more inclined towards cognitive science than "psychology" in the general sense.